Carbon budget of a shallow, lagoonal estuary: Transformations and source‐sink dynamics along the river‐estuary‐ocean continuum. (31st July 2017) - Crosswell, Joseph R.; Anderson, Iris C.; Stanhope, Jennifer W.; Van Dam, Bryce; Brush, Mark J.; Ensign, Scott; Piehler, Michael F.; McKee, Brent; Bost, Molly; Paerl, Hans W.
Abstract: A comprehensive carbon budget was constructed to quantify carbon flows through the freshwater‐marine continuum of a temperate, microtidal estuary. We performed coordinated measurements of dissolved inorganic carbon and total organic carbon fluxes to resolve spatial variability between and along the channel and shoals and diel variability across the entire estuary for 2 yr. Net ecosystem metabolism (NEM) was the most significant control on carbon flow within estuary regions. However, metabolic rates were spatially coupled such that counteracting fluxes across the channel‐shoal gradient or along the river‐ocean gradient resulted in system‐wide NEM that was closely in balance (–3.0 ± 3.3 to 1.1 ± 4.4 molC m −2 yr −1 ). Similarly, large diel and seasonal variability in air–water CO2 fluxes were observed during 72 spatial surveys, but these short‐term variations generally cancelled out when aggregated to annual budget terms. Although atmospheric exchanges were small (–0.2 ± 0.1 to 2.0 ± 0.4 molC m −2 yr −1 ), they were subject to large errors (± 4 molC m −2 yr −1 ) if diel variability was neglected. Internal mechanisms that maintained balanced carbon flows were strongly impacted by river discharge and were only apparent by separately quantifying channel and shoal fluxes. Notably, metabolic responses of the shoal to river forcing outweighed the responses of the channel, and the net impact was contrary to prior relationships derived from synthesis of lower‐resolution carbon budgets. Our budget demonstrates that resolution of carbon fluxes at appropriate scales, including channel‐shoal and diel variability, is critical to characterizing ecosystem function and the fate of carbon within the river‐ocean continuum.